CONCEPT OF LEADERSHIP IN PRAMOEDYA ANANTA TOER’S THE KING, THE WITCH, AND THE PRIEST (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2013)
This  journal  is entitled  Concept of Leadership  in  Pramoedya Anantoer’s  The King, The Witch, and The Priest. In this study, I  emphasized discussion on the leadership concept and its effects to the people in this narration. This study discusses three problems; they are (1) how is the leaders depicted in this novel? (2) What is the leadership concept depicted in this novel? (3) What are the effects of the leadership concept applied to the people’s betterment in this novel? I used Pramoedya Ananta Toer’s novel entitled  The King, The Witch, and The Priest  as the primary data and some references from books and websites dealing with leadership concept as the secondary data. The data were gained by reading closely the novel, then identifying data from the novel, inventorying the data, classifying the data, selecting the data, building up the main topic of the narration that in leadership, and reporting the data. The analysis of this study used new criticism approach in order to find,  identify and analyze the data from the novel. In addition, sociology approach was also used to support the analyses and answer the statements of the problem. From the data analysis I concluded that (1) the main characters had sense of leadership which was  built up by the environment (2) there are six points of leadership concept which is depicted in this novel; they are the characterization of a leader, ideal relationship between formal and informal leaders, focus on leadership, problem solving, delegation, and transformational leadership (3) there are some improvements for the people because of the application of leadership concept by the leaders in the novel. In general, this study is expected to be useful for the readers who would analyze a literary  work. I expected that this analysis could give new horizon to the readers about how to analyze a literary work according to the people’s attitudes and condition which are sometimes raised by an author.